Neoadjuvant Chemotherapy Versus Adjuvant Chemotherapy for Very Low-Lying Clinical T3 Rectal Cancer: The NAIR Phase 2/3 Randomized Clinical Trial - Yuichiro Tsukada, MD, PhD; Norio Saito, MD, PhD; Yuji Nishizawa, MD, PhD; Riki Ohno, MD, PhD; Fumihiko Fujita, MD, PhD; Keiji Koda, MD, PhD; Masayuki Ohue, MD, PhD; Eiji Shinto, MD, PhD; Akihiko Murata, MD, PhD; Yoshikazu Koide, MD, PhD; Koji Ikeda, MD, PhD; Hideaki Bando, MD, PhD; et al. (Annals of Surgery Open, 2025)
Objective:. To determine whether neoadjuvant chemotherapy (NAC) followed by total mesorectal excision (TME) and adjuvant chemotherapy (AC) is superior to TME followed by AC for very low-lying clinical (c) T3 rectal cancer. Background:. Preoperative radiation is widely used for preoperative treatment of cT3 rectal cancer; however, it worsens patient-reported outcomes (PROs). Preoperative treatment without radiation is expected to preserve PROs. Methods:. Patients with cT3N-anyM0 rectal cancer located within 5 cm from the anal verge were randomly assigned (1:1) to the NAC group (3 months of NAC followed by TME and 3 months of AC) or AC group (TME followed by 6 months of AC). NAC and AC comprised mFOLFOX6 (oxaliplatin, l-folinic acid, and fluorouracil) or CAPOX (oxaliplatin and capecitabine). The primary endpoint was the 3-year recurrence-free survival (RFS). PROs were analyzed. Results:. Between February 2013 and March 2019, 130 patients were randomly assigned to the NAC (n = 65) or AC (n = 65) groups; of these, 127 were evaluable (NAC, n = 65; AC, n = 62). At a median follow-up of 37.4 months, the 3-year RFS was 75.5% and 70.9% in NAC and AC groups, respectively [hazard ratio (HR) = 0.67, 60% confidence interval (CI) = 0.48–0.86, 95% CI = 0.34–1.32; P = 0.098 by log-rank test] and the primary endpoint was met. There was no significant intergroup difference in the local recurrence rate (LRR) or overall survival. Histologically, good responders to NAC showed a trend toward better RFS than poor responders. The study groups showed similar PROs. Conclusions:. NAC for very low-lying cT3 rectal cancer improved RFS without worsening PROs although LRR remained high. Trial Registration:. UMIN Clinical Trials Registry: UMIN000009510/Japan Registry of Clinical Trials: jRCTs031180278.